2019
DOI: 10.1111/jtxs.12405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gelling properties and flow behaviors of microbial transglutaminase (MTGase) and pectin modified fish gelatin

Abstract: The gelling and structural properties of microbial transglutaminase (MTGase) and pectin modified fish gelatin were compared to investigate their performances on altering fish gelatin properties. Our results showed that within a certain concentration, both MTGase and pectin had positive effects on the gelation point, melting point, gel strength, textural, and swelling properties of fish gelatin. Particularly, low pectin content (0.5%, w/v) could give fish gelatin gels the highest values of gel strength, melting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…The TPA test can better imitate the actions applied to the gel by the tongue and teeth compared with the gel strength test (Huang, Zhao, Fang, Lu, & Zhang, 2019). Four parameters including the hardness, springiness, cohesiveness, and chewiness were shown in Table 1.…”
Section: Texture Profile Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The TPA test can better imitate the actions applied to the gel by the tongue and teeth compared with the gel strength test (Huang, Zhao, Fang, Lu, & Zhang, 2019). Four parameters including the hardness, springiness, cohesiveness, and chewiness were shown in Table 1.…”
Section: Texture Profile Analysismentioning
confidence: 99%
“…Gel strength is an indicative to evaluate proteins' aggregation ability (Huang et al, 2019). It was determined by two indexes, breaking force and breaking deformation.…”
Section: Breaking Force and Breaking Deformationmentioning
confidence: 99%
“…However, there was no significant difference in the springiness and cohesiveness of all of the gels. Huang, Zhao, et al () also found that different concentrations of MTGase and pectin had no significant effects on the springiness and cohesiveness of fish gelatin. Springiness is the extent to which the colloid can be recovered after the first compression and is an indication of a gel's “rubberiness” in the mouth.…”
Section: Resultsmentioning
confidence: 96%
“…However, there was no significant difference in the springiness and cohesiveness of all of the gels. Huang, Zhao, et al (2019) also found that different concentrations of MTGase and pectin had no significant effects on the springiness and cohesiveness of fish gelatin.…”
Section: Texture Propertiesmentioning
confidence: 89%
See 1 more Smart Citation